The Role of Systemic Treatment and Radiotherapy in Malignant Mesothelioma - Lind, Michael; Barton, Rachael; Wieczorek, Andrzej; Loubani, Mahmoud; A. Kastelik, Jack (Current Respiratory Medicine Reviews, 2016)
There has been an increase in understanding molecular biology of malignant pleural mesothelioma. This resulted in more clinical trials of novel therapeutic approaches. The more conventional systemic treatments for malignant mesothelioma are based on the use of Cisplatin and Pemetrexed. The newer agents such as vorinostat an Histone deacetylase inhibitor, focal adhesion kinase inhibitor Defactinib, mTOR inhibitor Everolimus, Bevacizumab a monoclonal antibody directed against Vascular Endothelial Growth Factor, immune check-point inhibitors, mesothelin targeted antibodies, Amatuximab have been investigated for their potential role in treatment of malignant mesothelioma. The role of radiation therapy in the curative treatment of malignant pleural mesothelioma has not been conclusively determined. In this review we will discuss the application of both radical and palliative radiotherapy in the context of managing of malignant mesothelioma.
Keywords: malignant mesothelioma